1995
DOI: 10.1126/science.270.5236.610
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Complexity of Phospholipid Monolayers Investigated by Near-Field Scanning Optical Microscopy

Abstract: Near-field scanning optical microscopy of phospholipid monolayers doped with fluorescent lipid analogs reveals previously undescribed features in various phases, including a concentration gradient at the liquid-expanded/liquid-condensed domain boundary and weblike structures in the solid-condensed phase. Presumably, the web structures are grain boundaries between crystalline solid lipid. These structures are strongly modulated by the addition of low concentrations of cholesterol and ganglioside GM1 in the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 26 publications
7
138
0
2
Order By: Relevance
“…This was illustrated by Hwang et al, where high resolution near-field fluorescence measurements revealed new structures in lipid monolayers of L-␣-dipalmitoylphosphatidylcholine ͑DPPC͒ doped with cholesterol and ganglioside G M 1 . 31 Following these results, we have shown that the phase partitioning in DPPC monolayers can be unambiguously assigned by comparing the small height differences ͑5 to 8 Å͒ observed in the near-field force image with the near-field fluorescence image. 39,40,44 We also showed that for model lipid bilayers, NSOM can uniquely probe the phase partitioning on either side of the membrane with nanometric resolution.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…This was illustrated by Hwang et al, where high resolution near-field fluorescence measurements revealed new structures in lipid monolayers of L-␣-dipalmitoylphosphatidylcholine ͑DPPC͒ doped with cholesterol and ganglioside G M 1 . 31 Following these results, we have shown that the phase partitioning in DPPC monolayers can be unambiguously assigned by comparing the small height differences ͑5 to 8 Å͒ observed in the near-field force image with the near-field fluorescence image. 39,40,44 We also showed that for model lipid bilayers, NSOM can uniquely probe the phase partitioning on either side of the membrane with nanometric resolution.…”
Section: Introductionmentioning
confidence: 54%
“…[26][27][28][29] Extensive studies have characterized the phase partitioning in these films and the effects that biologically relevant additives such as cholesterol and small peptides can have on membrane properties. 30,31 Often, these effects can be observed by monitoring changes in the film structure using high resolution techniques such as fluorescence microscopy, 27,28,32 scanning probe microscopy, [33][34][35][36][37] or electron microscopy. 38 Recently, our group and others have illustrated the utility of NSOM for these types of measurements, which has resulted in the observation of new structures and processes at the submicron level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely targets for water bonding are the oxygen atoms of phosphate and carbonyl groups of gangliosidic sialic acid residue. Phospholipid morphology of the membrane is affected by the presence of water in this residue [19]. A marked increase in water permeability, about 30-100 fold, was found as a bilayer passed through a temperaturedependent phase transition, but water permeability was not strongly influenced by hydrocarbon chain length or unsaturation so long as bilayer was fluid [20].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence NSOM experiments have been used to observe the spatial localization of fluorescent species in composites, 205 to investigate lipid layer structures 206 and their evolution, 207 to probe biological membranes and membrane proteins, 208 to detect isolated chromophores, 209 to monitor variations in sample properties brought about by aggregation phenomena, 210 and to investigate the photophysical properties of organic semiconductors. 211 Fluorescence resonance energy transfer experiments performed using NSOM have provided particularly dramatic resolution of energy transfer processes occurring across interfaces One of the significant promises of NSOM is the development of chemical imaging based on vibrational spectroscopic data acquired with nanometer-scale spatial resolution.…”
Section: Near-field Scanning Optical Microscopymentioning
confidence: 99%